(untitled) (Research, Society and Development, 2021)
Introduction: Zika Virus Congenital Syndrome (SCZV) is classified as a rare congenital infection, associated with microcephaly, intracranial calcifications, eye changes, congenital clubfoot, spasticity and hypertonia, requiring monitoring by the health team, especially physiotherapists. Methodology: A literature review was carried out through a bibliographic survey in the electronic databases Scientific Electronic Library Online (SciELO), Virtual Health Library (VHL Regional Portal) and National Library of Medicine (PubMed), articles and books on Google Scholar with a focus on the theme. Using the following descriptors: Rehabilitation AND Zika Virus Infection OR Zika Virus AND Microcephaly AND child AND Physical Therapy Specialty. Results: 307 studies were identified, with 10 studies being eligible and after reading 5 of them were excluded, therefore, 5 studies were selected for this review. Conclusion: Although the studies reported in this review show that physical therapy has brought motor benefits, further studies on the topic are still needed, given that the syndrome causes neuropsychomotor changes and there is a scarcity of studies demonstrating the effects of the physiotherapy techniques employed.